Alternative liming blends for fish culture - Mikaely Karine Barbosa Nobre; Francisco Roberto dos Santos Lima; Frederico Batista Magalhães; Marcelo Vinícius do Carmo e Sá (Acta Scientiarum. Animal Sciences, 2014)
Calcium carbonate (limestone) is a safe but slow-acting product for aquaculture liming. Calcium oxide (lime) is a fast-acting but dangerous product. It would be interesting to have simultaneously a safe and fast-acting liming product. The present work aimed to evaluate two alternative liming blends for tilapia culture. The culture water was initially acidified with HCl. Next, the same quantity of CaCO3 (control), Na2CO3+CaSO4 or Na2CO3+CaCl2 was applied to the culture water. There were also non-limed tanks. One hundred and twenty Nile tilapia juveniles (1.6 ± 0.1 g) were stocked in twenty 250-L culture tanks for 10 weeks. All products used were similarly efficient in increasing the alkalinity of water. The probable better environment for algal growth in the limed tanks caused an increase in the DO2 concentrations and a decrease in CO2, total ammonia nitrogen, nitrite and phosphorus, in relation to the non-limed tanks. The highest final body weight of fish was observed in the Na2CO3+CaCl2 tanks. The lowest final body weight was verified in the CaCO3 tanks. It was concluded that the alternative blend of Na2CO3 plus CaCl2 is a better liming product than the standard CaCO3 for Nile tilapia culture.